The effectiveness of connective tissue massage in the treatment of primary dysmenorrhea among young women Efetividade da massagem do tecido conjuntivo no tratamento da dismenorréia primária em mulheres jovens - Conceição Aparecida de Almeida Santos Reis; Ellen Hardy; Maria Helena de Sousa (Instituto Materno Infantil de Pernambuco, 2010)
OBJECTIVE: to evaluate the possible effectiveness of connective tissue massage for the non-medical treatment of primary dysmenorrhea. METHODS: this was a pilot observational cohort study. SETTING: University clinics. PARTICIPANTS: Seventy two young women presenting primary dysmenorrhea. INTERVENTION: Physiotherapy students in their last year at university and physiotherapists were trained for 20 hours to apply the massage. All volunteers were submitted to lumbar connective tissue massage twice weekly, while they were not menstruating, during the three menstrual cycles that followed admission. The following regions were manipulated: sacral, lumbar, last thoracic vertebrae and subcostal. INDICATORS: Pain score, use of pain medication and other menstrual systemic symptoms over time (before treatment, after each of the three menstrual periods during treatment, and in the second and in the third month following treatment). RESULTS: after the first treatment month, the pain score decreased significantly (p<0.001). The percentage of women requiring pain medication and reporting systemic symptoms decreased over time, although there was no correlation between the number of massages and the pain score in the multiple regression analysis. CONCLUSIONS: connective tissue massage may cause a reduction in menstrual pain but the study design does leaves open the possibility of a placebo effect. The results justify performing a randomized clinical trial to confirm whether such an effect exists or not. OBJETIVO: avaliar a possível efetividade da massagem do tecido conjuntivo para o tratamento não medicamentoso da dismenorréia primária. MÉTODOS: estudo piloto, do tipo observacional de coorte com setenta e duas mulheres jovens com dismenorréia primária em Clínica Universitária. Estudantes de fisioterapia e fisioterapeutas receberam treinamento de 20 horas para aplicar a massagem. Todas as voluntárias receberam massagem do tecido conjuntivo lombar duas vezes por semana, no período intermenstrual durante os três ciclos menstruais após a admissão. As regiões manipuladas foram: sacral, lombar, última vértebra torácica e sub-costal. Desfechos avaliados: Escore de dor, uso de medicamentos e ocorrência de outros sintomas sistêmicos ao longo do tempo (antes do tratamento, após cada ciclo menstrual durante o tratamento e nos dois meses após o tratamento). RESULTADOS: o escore de dor diminuiu significativamente após o primeiro mês de tratamento (p<0,001). A porcentagem de voluntárias que precisou de medicamentos para dor e que relatou sintomas sistêmicos diminuiu com o tempo de tratamento, mas não houve correlação entre o número de massagens e o escore de dor na análise multivariada. CONCLUSÃO: a massagem do tecido conjuntivo pode causar uma redução da dor menstrual, mas o tipo de estudo não permite excluir um efeito placebo. Os resultados justificam a realização de estudo clínico randomizado para confirmar ou não esse efeito.